2017
DOI: 10.2106/jbjs.cc.16.00114
|View full text |Cite
|
Sign up to set email alerts
|

Rice Bodies and a Partial Flexor Tendon Rupture in a Patient with Juvenile Idiopathic Arthritis

Abstract: JIA is one of the most common rheumatologic conditions of childhood. Establishing the diagnosis can be challenging in very young children, particularly when clinical presentation is atypical and serology is negative. Surgical intervention may be warranted in the appropriately selected patient with JIA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Indeed, only a few cases of children with JIA accompanied by rice bodies have been reported. [3][4][5][6][7][8][9][10][11][12] And they all fulfilled the 2001 International League of Associations for Rheumatology (ILAR) classification criteria. 13 We summarized the clinical manifestations, laboratory tests, and treatment modalities (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, only a few cases of children with JIA accompanied by rice bodies have been reported. [3][4][5][6][7][8][9][10][11][12] And they all fulfilled the 2001 International League of Associations for Rheumatology (ILAR) classification criteria. 13 We summarized the clinical manifestations, laboratory tests, and treatment modalities (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…However, patients might occasionally have normal serologic results and have no primary complaint of joint involvement. 8 Nabet et al 9 reported a seronegative case of JIA with proliferative flexor tenosynovitis, but without joint involvement. The patient in our case had normal serologic results and no joint involvement.…”
Section: Discussionmentioning
confidence: 99%
“…Rice bodies indicate the presence of chronic synovial inflammation, such as rheumatoid arthritis (RA) and tuberculosis arthritis. While rice bodies are relatively common in adult patients with RA, they are much less frequent in children 2 and can often affect the tendons, leading to rupture 3,4 . The patient is currently treated with methotrexate and is well, without any sign of disease progression.…”
mentioning
confidence: 99%